Klasifikasi Data Penjualan Dengan Metode K-Nearest Neighbor Pada Pt. Terang Abadi Raya - Novitadewi, Ni Made Ary; Sugiartawan, Putu; Fittryani, Yuri Prima (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
PT. Terang Abadi Raya is a lighting company engaged in trading, with the many types of products to be sold the company has difficulty determining which product sells the most on the market. Making it difficult for the marketing department to offer products to be sold. PT. Terang Abadi Raya has various types of lighting products based on sales data for the last 1 year, using the K-Nearest Neighbor (K-NN) prediction to make it easier for companies to plan sales. To find out the best-selling sales using sales data classification and the K-Nearest Neighbor (K-NN) method, of the 19,290 items classified, the graphic results obtained were 12,420 categorized as best-selling labels, and 6,870 categorized as not-selling labels.